Madihin of John Tralala and Hendra: A Study of Presentation, Structure, Form, Value, and Function - Rafiek, M. (Soegijapranata Catholic University, 2019)
Abstract: This study aims to describe and explain about (1) the structure of the presentation of madihin, (2) the forms of madihin, (3) the values in madihin, and (4) the functions in madihin that were performed by pamadihinan John Tralala and Hendra. This study used Parry and Lord and oral literary approach and it was qualitative research type. The oral literary approach was used to study Madihin's oral literature in terms of presentation structure, form, value, and function. As an oral literature, Madihin can be described qualitatively because the data is submitted verbally by the pamadihinan (someone who presents madihin). After that, the madihin data is discussed in accordance with its presentation structure, form, value, and function. The results of this study are (a) the presentation structure consists of opening, installing tabi, presenting the contents (manguran), and closing; (b) the forms of madihin of John Tralala and Hendra are (1) sampiran, (2) question and answer or question and answer sentence, (3) poem, (4) poem of more than 4 lines and broken rhymes, (5) broken rhyming poem, (6) poem of less than 4 lines, and (7) Answers. So, there are 7 forms of Madihin of John Tralala and Hendra; (c) the values in madihin of John Tralala and Hendra are (1) the value of loving art, (2) the value of preservation, (3) the value of working together, (4) the value of art appreciation, (5) the value of hard work, (6) the value of honesty, (7) the value of self-confidence or self-flattering, (8) the value of